(untitled) (Veterinary Science, 2017)
Pregnancy in sows lasts 114 ± 3 days and has a placenta epitheliochorial, diffuse, folded, non invasive and adecidua. The proper interaction between peri-implanted embryo and the maternal endometrium would be under the control of cytokine especially paracrines. The aim of this work was to study the presence of IFN-g, IL-6, IL-12, IL-15 and IL-18 in sera and in extracts of maternal (HoPM) and fetal (HoPF) placenta from sows of different gestational periods. Some samples of reproductive tracts from 61 swines between 30 and 114 days of gestation, and nonpregnant sows were used. It was determined the concentration of interferon-g, IL-6, IL- 12, IL-15 and IL-18 by solid-phase ELISA. IFN-g, IL-6 and IL-12 showed a peak at 32 days of gestation only in the fetal placental extracts. IL-15 remained high during pregnancy, decreasing at term. IL-18 was found in fetal placental extracts between ± 60-70 days of pregnancy. In conclusion, the presence of IL-6 on day 32 would mark the correct establishment of pregnancy, contributing its presence the beginning of the development of the immune system and fetal ossification. It is suggested that IL-15 stimulate the synthesis of IgG, whereas IL- 12, IL-15 and IL-18 together IFN-g at specific times of gestation, would indicate the role of the innate immune system in swine pregnancy.